Gestión administrativa y su efecto en la rentabilidad financiera de la empresa comercial el Trébol SAC. del distrito de Trujillo, 2016 - Merino Tapia, Rafael Domingo (2017)
ABSTRACT The purpose of the investigation was to determine the effect of administrative management on the financial profitability of the commercial company Trébol SAC. The financial profitability of the company reflects the return on investments in the profits obtained by investing money in financial resources, that is, the return that is obtained as a result of making investments. We worked as a sample to the company El Trebol SAC. The one that was constituted by 05 workers (managers of the area of finance) to be quite representative and adequate with the object of study, which was selected at the discretion of the investigator using the technique of the survey. Likewise, the analytic-synthetic, inductive-deductive, statistical methods were used. It is concluded that the administrative management has significant effect on the financial profitability of your company. It is recommended that the company Trebol should continue to perform good administrative management; Because not doing so would be incurring inadequate processes, techniques and procedures would lead to higher expenses affecting profitability.